Europe 2020 - a promising strategy? - Christian Egenhofer; Luc Soete; Karel Lannoo; László Csaba; Iain Begg; Philippe Pochet; Annette Bongardt; Francisco Torres (Intereconomics, 2010)
In March, the European Commission released its Europe 2020 strategy proposal, which strives for smart, sustainable and inclusive growth and greater policy coordination between the EU and national governments. While the document was greeted with scepticism in some quarters, others believe it lays out the path to continued European prosperity and social cohesion. This Forum examines the strengths and weaknesses of the strategy.
Keywords: 330